Education to prevent stunting and innovation of 'SABI nuggets' as a complementary food in Silaberanti Village, Palembang - Sutrisno Sutrisno; Muhammad Abdul Rasyid; Rani Isna Yuniar; Nota Lisa Firani; Putri Wijaya; Fisia Iwanda; Rikek Rihdola; Riya Safitri; Rya Sanda; Ryan Hadi Saputra; Kezya Calista Gliselda Frans (Community Empowerment, 2024)
Stunting remains a pressing health concern that demands attention from all members of society. In Palembang City, the number of stunting cases has risen alarmingly from 100 in 2023 to 224. The root causes lie in limited knowledge about balanced nutrition and a tendency to consume unhealthy fast food. This community service initiative aimed to enhance awareness about the significance of adopting healthy food management practices as a strategy to combat stunting. The project employed a Participatory Rural Appraisal (PRA) approach, encompassing socialization, training, and mentorship. The intervention yielded remarkable results, with knowledge levels among participants increasing from 65% to 95%. This demonstrates the effectiveness of the training in empowering the community with knowledge about balanced nutrition, healthy and nutritious meals for children, and stunting prevention strategies. Furthermore, the community demonstrated creativity by developing an innovative food supplement called "SABI nuggets," made from patin fish and carrots.